Investigation of the effects of chronic hypertrophic adenotonsillitis on olfaction and quality of life - Güçlü, Oğuz; Yazıcı, İbrahim and Toroslu, Tolgahan and Sefa Dereköy, Fevzi (ENT Updates, 2013)
Objective: To investigate the effects of the chronic hypertrophic adenotonsillitis on olfaction and quality of life. Methods: Pediatric patients, aged 7-8 years, were prospectively included in three groups; Group I- Adenotonsillar diseases (n=15), Group II- Control (n=15) and Group III- Postoperative group (n=15). Patients were evaluated with the Sniffin’ Sticks 12 item smell identification test and obstructive sleep disorder-6 (OSD-6) quality of life survey. Results: Total smell identification (SI) scores were 6.93±1.75 in the adenotonsillar disease, 8.73±1.10 in the control and 7.67±1.59 in the postoperative groups, respectively. Total SI score in the adenotonsillar disease group was significantly lower than the control group (p<0.05). Conclusion: Adenotonsillar diseases affect both quality of life and smell function. Six months after surgery quality of life reaches normal standards. Smell function is observed to have partially recovered by the sixth month. This situation may be due to obstructive symptoms resolving in the early postoperative period, while symptoms related to mucosal or inflammatory pathologies recover more slowly.